2019
DOI: 10.12740/app/109629
|View full text |Cite
|
Sign up to set email alerts
|

Family and peer resources in relation to psychological condition in patients with paranoid schizophrenia

Abstract: Aim of the study:The main objective of this study was seeking for the predictive role of social resources in maintaining the psychological condition by adults suffering from paranoid schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The 33 samples were considered individual studies for conducting the meta-analysis. Table 1 States, three were conducted in Mexico (Cardona, 2015;Martinez-Pampliega et al, 2017), two were conducted in Poland (Izydorczyk et al, 2019;Jelonkiewicz, 2010), two were conducted in Spain (Castillo et al, 2004;Penas et al, 2020), and one study was conducted in China (Xia et al, 2004). One study included a sample of American and Taiwanese study participants (Lin & Chen, 1994).…”
Section: Study Selectionmentioning
confidence: 99%
“…The 33 samples were considered individual studies for conducting the meta-analysis. Table 1 States, three were conducted in Mexico (Cardona, 2015;Martinez-Pampliega et al, 2017), two were conducted in Poland (Izydorczyk et al, 2019;Jelonkiewicz, 2010), two were conducted in Spain (Castillo et al, 2004;Penas et al, 2020), and one study was conducted in China (Xia et al, 2004). One study included a sample of American and Taiwanese study participants (Lin & Chen, 1994).…”
Section: Study Selectionmentioning
confidence: 99%
“…Jafri (2017) found that PsyCap is one of the most potent predictors of students' motivation. It substantially supports the development of well-being in people functioning in severe stress situations (Izydorczyk et al, 2019). PsyCap was closely related to higher intrinsic motivation and identified regulation, but it was also associated with lower levels of amotivation (Datu et al, 2018).…”
Section: Psychological Capital To Teacher Well-being Work Task Motiva...mentioning
confidence: 66%